Longitudinal monitoring of the development of antifilarial antibodies and acquisition of Wuchereria bancrofti in a highly endemic area of Haiti. - Katy L Hamlin; Delynn M Moss; Jeffrey W Priest; Jacquelin Roberts; Joseph Kubofcik; Katherine Gass; Thomas G Streit; Thomas B Nutman; Mark L Eberhard; Patrick J Lammie (Public Library of Science (PLoS), 2012)
Antifilarial antibody testing has been established as a sensitive and specific method of diagnosing lymphatic filariasis. However, the development of serological responses to specific filarial antigens and their relationship to acquisition of infection is poorly understood. In order to evaluate whether the development of antigen specific antifilarial antibodies precedes microfilaremia and antigenemia, we compared the antibody responses of serum samples collected between 1990 and 1999 from a cohort of 142 Haitian children followed longitudinally. Antigen status was determined using the Og4C3 ELISA and the presence of microfilaremia was detected using microscopy. Antibody responses to Wb123, a Wuchereria bancrofti L3 antigen, were measured using a Luciferase Immunoprecipitation System (LIPS) assay. Antibody responses to Bm14 and Bm33, Brugia malayi antigens and to a major surface protein (WSP) from Wolbachia were analyzed using a multiplex bead assay. Over follow-up, 80 (56%) of the children became antigen-positive and 30 (21%) developed microfilaremia. Detectable antibody responses to Bm14, Bm33, Wb123, and WSP developed in 95%, 100%, 92%, and 29% of children, respectively. With the exception of WSP, the development of antibody responses generally preceded detection of filarial antigen. Our results show that antifilarial antibody responses can serve as an important epidemiological indicator in a sentinel population of young children and thus, may be valuable as tool for surveillance in the context of lymphatic filariasis elimination programs.